Evaluation of agraz consumption on adipocytokines, inflammation, and oxidative stress markers in women with metabolic syndrome (2018)
ABSTRACT: Metabolic syndrome (MetS) is characterized by increased oxidative stress and a pro-inflammatory state. Vaccinium meridionale Swartz (known as “agraz”) is a berry rich in polyphenolic compounds with demonstrated antioxidant activity and anti-inflammatory effects in preclinical studies. The aim of this study was to evaluate the effects of agraz consumption on inflammatory and oxidative stress markers in women with MetS. Forty women with MetS (47 ± 9 years) were randomly assigned to consume daily either 200 mL of agraz nectar or placebo over four weeks in a double-blind, cross-over design study, separated by a 4-week washout period. Metabolic and inflammatory markers in serum and antioxidant/oxidative stress markers in serum and urine were assessed at the end of each period. Serum antioxidant capacity measured by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method was significantly higher (p = 0.028), while urinary 8-hydroxy-2-deoxyguanosine (8-OHdG) was lower (p = 0.041) after agraz consumption, compared to placebo. In conclusion, consumption of agraz during four weeks increased serum antioxidant capacity and decreased a marker of DNA oxidative damage in women with MetS, compared to placebo. These results suggest that agraz consumption may play a protective role in patients with MetS.